Sir Frederic William Burton and the Rosebery Minute: the directorship of the National Gallery, London, in the late nineteenth century - Greer, Elena J. (2017)
This thesis examines for the first time the role of Sir Frederic William Burton (1816-1900) as director of the National Gallery, London, during the period 1874 to 1894. I argue that his directorship is important because it was followed by the second major administrative re-organisation in the Gallery’s history, namely the Rosebery Minute of 1894, which significantly reduced the authority of the director in making acquisitions. This power had been bestowed upon the director in 1855 after an in-depth parliamentary Select Committee examining the running of the Gallery, which had established the post for the first time. My thesis seeks to determine to what extent and how Burton’s tenure prompted this major reassessment of the Gallery’s management structure. The enquiry addresses the question from a variety of perspectives including Burton’s acquisitions, the display of the collection, his attitude to the social function of the Gallery and the relationship of the Gallery authorities with government departments and individuals.